A distal super-enhancer activates oncogenic ETS2 via recruiting MECOM in inflammatory bowel disease and colorectal cancer - Yongheng Chen; Ying Ying; Maolin Wang; Canjie Ma; Min Jia; Liang Shi; Shilan Wang; Xiangyi Zheng; Wei Chen; Xing-sheng Shu (Cell Death and Disease, 2023)
Abstract Abnormal activities of distal cis-regulatory elements (CREs) contribute to the initiation and progression of cancer. Gain of super-enhancer (SE), a highly active distal CRE, is essential for the activation of key oncogenes in various cancers. However, the mechanism of action for most tumor-specific SEs still largely remains elusive. Here, we report that a candidate oncogene ETS2 was activated by a distal SE in inflammatory bowel disease (IBD) and colorectal cancer (CRC). The SE physically interacted with the ETS2 promoter and was required for the transcription activation of ETS2. Strikingly, the ETS2-SE activity was dramatically upregulated in both IBD and CRC tissues when compared to normal colon controls and was strongly correlated with the level of ETS2 expression. The tumor-specific activation of ETS2-SE was further validated by increased enhancer RNA transcription from this region in CRC. Intriguingly, a known IBD-risk SNP resides in the ETS2-SE and the genetic variant modulated the level of ETS2 expression through affecting the binding of an oncogenic transcription factor MECOM. Silencing of MECOM induced significant downregulation of ETS2 in CRC cells, and the level of MECOM and ETS2 correlated well with each other in CRC and IBD samples. Functionally, MECOM and ETS2 were both required for maintaining the colony-formation and sphere-formation capacities of CRC cells and MECOM was crucial for promoting migration. Taken together, we uncovered a novel disease-specific SE that distantly drives oncogenic ETS2 expression in IBD and CRC and delineated a mechanistic link between non-coding genetic variation and epigenetic regulation of gene transcription.